Human-directed gazing behaviour in puppies and adult dogs, Canis lupus familiaris - C. Passalacqua; S.R. Marshall; E. Prato Previde Albrisi Colomban; S. Barnard; G. Lakatos; P. Valsecchi (Animal Behaviour, 2011)
Recent evidence indicates that dogs' sociocognitive abilities and behaviour in a test situation are shaped by both genetic factors and life experiences. We used the 'unsolvable task' paradigm to investigate the effect of breed and age/experience on the use of human-directed gazing behaviour. Following a genetic classification based on recent genome analyses, dogs were allocated to three breed groups, namely Primitive, Hunting/Herding and Molossoid. Furthermore, we tested dogs at 2 months, 4.5. months and as adults. The test consisted of three solvable trials in which dogs could obtain food by manipulating a plastic container followed by an unsolvable trial in which obtaining the food became impossible. The dogs' behaviour towards the apparatus and the people present was analysed. At 2 months no breed group differences emerged and although human-directed gazing behaviour was observed in approximately half of the pups, it occurred for brief periods, suggesting that the aptitude to use human-directed gazing as a request for obtaining help probably develops at a later date when dogs have had more experience with human communication. Breed group differences, however, did emerge strongly in adult dogs and, although less pronounced, also in 4.5-month-old subjects, with dogs in the Hunting/Herding group showing significantly more human-directed gazing behaviour than dogs in the other two breed groups. These results suggest that, although the domestication process may have shaped the dog's human-directed communicative abilities, the later selection for specific types of work might also have had a significant impact on their emergence.